Deformation and Yield of Polymer Thin Films in Confined Geometries - BRAZIL, OWEN (Trinity College Dublin. School of Physics. Discipline of Physics, 2019)
Polymer thin film mechanics represents a hugely promising field of research. Due to their versatility and ease of fabrication, polymer films and coatings rank among the most ubiquitous systems in all of nanotechnology. The ability to correctly characterise and mechanically pattern such small volumes of material is a significant step towards the development of the next generation of organic nanomechanical systems. In this work, the deformation and yield of polymer films is studied through a series of flat punch indentation and imprint experiments, where the film material becomes geometrically confined beneath features whose width are many times the initial thickness of the film. A new methodology is developed for the extraction of the mechanical properties of supported thin films. Indentation of a polymer film by a well-aligned cylindrical flat punch whose diameter is several times the initial thickness of the film results in a state of uniaxial strain deformation, wherein lateral displacements are suppressed by the surrounding film. This method, called the confined compression layer test, allows for extraction of Young’s modulus, Poisson’s ratio, and the bulk modulus in a single test. Further, the test leads to a distinct confined yield event throughout the volume beneath the punch, in the absence of lateral flow. This yield event occurs within a highly uniform, pressure dominated stress field that is entirely unique at the nanoscale. The confined layer compression test is characterised here via indentation of atactic polystyrene films of 190 – 470 nm thicknesses with a 2050 nm diameter diamond flat punch and via finite element simulations. The test is also demonstrated in PMMA and amorphous selenium films. The confined layer compression test is then extended to study aspects of non- equilibrium glass mechanics in polymer thin films. The effect of thermal history on the intrinsic stress-strain behaviour of polystyrene films is characterised, with well annealed films exhibiting higher confined yield stresses and greater resistance to plastic deformation. The effect of confined plasticity on the viscoelastic properties of polystyrene is studied, with a notable increase in creep compliance observed at yield. This is linked to higher segmental mobility. An increase in yield stress for materials plastically deformed in the confined layer compression test is reported. This phenomenon is studied experimentally in polystyrene and via finite element simulations and is found to result from persistent residual stresses imparted to the material during confined yield. These residual stresses also result in an elastic densification of the confined material, with a maximum relative mass density increase of 3.4% being observed in a 203 nm polystyrene film indented to 0.84 GPa peak stress. This technique suggests the possibility of a new form of residual stress based mechanical lithography. Finally, a significant improvement to the thermal nanoimprint technique is introduced. Shear flow of resist material confined directly beneath large aspect ratio imprint mold features is enhanced by the addition of a small (~10% of the feature size), oscillating lateral strain during normal loading. This leads to greater plasticity beneath mold features and a pumping action which aids flow into the surrounding cavities. This is demonstrated to enable high fidelity imprint below the glass transition temperature in 50 μm thick PMMA sheets, while significant improvements are also reported in 150 and 40 nm films imprinted with a 4 μm full pitch line pattern mold of 35 nm relief. The technology, called small amplitude oscillatory shear forming, is shown to enable low temperature, high fidelity pattern transfer over macroscopic sample areas, typically on the order 1 x 1 cm with a variety of mold geometries. In summary, this work sets out to use stress and strain as control variables to extend our knowledge and understanding of glassy polymer films and find new ways of patterning and probing materials at small scales.
APPROVED
Keywords: Nanomechanics; Thin films; Polymers